Zinc, magnesium, and calcium ion supplementation confers tolerance to acetic acid stress in industrial Saccharomyces cerevisiae utilizing xylose. Issue 12 (29th July 2014) - Ismail, Ku Syahidah Ku; Sakamoto, Takatoshi; Hasunuma, Tomohisa; Zhao, Xin‐Qing; Kondo, Akihiko
Abstract Lignocellulosic biomass is a potential substrate for ethanol production. However, pretreatment of lignocellulosic materials produces inhibitory compounds such as acetic acid, which negatively affect ethanol production by Saccharomyces cerevisiae. Supplementation of the medium with three metal ions (Zn2+, Mg2+, and Ca2+) increased the tolerance of S. cerevisiae toward acetic acid compared to the absence of the ions. Ethanol production from xylose was most improved (by 34%) when the medium was supplemented with 2 mM Ca2+, followed by supplementation with 3.5 mM Mg2+ (29% improvement), and 180 μM Zn2+ (26% improvement). Higher ethanol production was linked to high cell viability in the presence of metal ions. Comparative transcriptomics between the supplemented cultures and the control suggested that improved cell viability resulted from the induction of genes controlling the cell wall and membrane. Only one gene, FIT2, was found to be up‐regulated in common between the three metal ions. Also up‐regulation of HXT1 and TKL1 might enhance xylose consumption in the presence of acetic acid. Thus, the addition of ionic nutrients is a simple and cost‐effective method to improve the acetic acid tolerance of S. cerevisiae.